Characterization of alcohol producing yeast isolated from fermented fruit juice of Sonneratia caseolaris - Thuoc, Doan Van; Hong Duyen, Dinh Thi (Academia Journal of Biology, 2015)
Twenty yeast strains were isolated from fermented fruit juice of Sonneratia caseolaris. Among them, strain NM2 was chosen for further study as a potential alcohol producer. The results of molecular analysis method show that yeast strain NM2 belongs to C. tropicalis, which is widely distributed in the tropical and subtropical marine environment. The optimum temperature and the initial pH value for alcohol fermentation of strain C. tropicalis NM2 were 30oC and 3.5, respectively. Under these conditions, after 14 days of fermentation of fruit juice of Sonneratia caseolaris, maximum alcohol level of 14.9% (v/v) was obtained by strain C. tropicalis NM2. With the potential of high alcohol production, the yeast strain C. tropicalis NM2 can be applied for industrial alcohol or bioethanol production.